Penerapan Teknologi Lubang Resapan Biopori sebagai Alternatif Pupuk Kompos dan Mengurangi Sampah Organik di Desa Kalibarumanis - Yudha Alif Auliya; Dejan Putra Pratama; Lulu Hamamadah; Bima Jati Kusuma; Wanda Puspita Sari (Jurnal Transformasi Digital Masyarakat (DIGIMAS), 2025)
Kalibarumanis Village, located in Kalibaru District, Banyuwangi, has significant potential as a coffee-producing areabut faces serious issues related to organic waste management. Through a community service program by KKN-UMD 301students from the University of Jember, a solution involving the implementation of Biopore Infiltration Holes (LRB) technologywas introduced to manage organic waste and improve soil fertility in coffee plantations. LRB facilitates the decomposition oforganic waste into compost and enhances water infiltration into the soil. This program includes socialization, training, andassistance in LRB installation in RT 06, 08, and RT 11 of Kalibarumanis Village, actively involving the community. The programresults show an increase in environmental awareness and community skills in independently managing organic waste. LRBinstallations also provide economic benefits using compost in coffee plantations, supporting local agricultural sustainability.Despite challenges in socialization and limited resources, community participation and continuous support have ensured theprogram's success. This initiative not only addresses waste management issues but also provides long-term benefits for thelocal environment and economy. The evaluation results of biopore application on coffee plants over three months indicated asignificant difference in leaf growth compared to coffee plants that did not utilize biopore.